Singles: The challenge for brands to understand their consumption through social network in Spain - Sebastián Morillas, Ana Belén; Martín Soldana, Irene (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Times have changed and we are living an authentic demographic and technological revolution, where the single, also called single, besides being synonymous of free, happy and rich, shows a high consumption of Internet and social networks. In Spain, they have become a community with a relevant consumption behavior for companies due to the growth that this social group is experiencing. Analyzing communication and marketing strategies, specifically those related to online shopping and social media consumption, is key for brands to connect with this target and offer them what they need.